Corruption, endogenous fertility, and growth - Cinyabuguma, Matthias (The Lahore journal of economics, 2011)
While much research in economic development has pointed out the negative impact of corruption on growth, less research has been devoted to studying the relationship between corruption and demographic transition. This theme is developed into an overlapping generation model in which corruption affects fertility decisions through its negative impact on physical capital formation and its productivity. The analysis indicates that, when the level of corruption is high, the productivity of capital is low and fertility is excessively high because of the relatively low cost of raising children. Theoretical and empirical results show that, in both developed and developing countries, corruption creates distortions and leads to low-equilibrium traps. Introducing child quality into the model accelerates the pace of demographic transition and produces effects similar to reducing the level of corruption. Empirical estimates confirm the predictions of the model and support the proposition that fertility declines in less corrupt countries. [PUBLICATION ABSTRACT]